Preservation of a split tooth: nonsurgical clinical management - Schürz, Alexander; Gehrig, Holger; Schüßler, Dorothée L.; Mente, Johannes (Journal of endodontics, 2020)
A tooth is considered to be a split tooth if it contains a fracture line extending from the occlusal surface through both marginal ridges. Currently, the only treatment option for a split tooth is extraction. The present case report describes a novel therapeutic strategy for the preservation of a split tooth (first maxillary premolar) with a fracture in the mesiodistal direction. A systematic nonsurgical procedure involving visualization and slight widening of the fracture line is described. This procedure facilitates sealing of the fracture gap with a biocompatible calcium silicate cement (mineral trioxide aggregate) as well as internal composite resin stabilization and cuspal coverage restoration of the tooth. A 3-year follow-up showed a promising clinical and radiographic outcome. The concept presented here is an alternative treatment option for a split tooth, which allows preservation of the tooth rather than its extraction.